Investigating the Influence of Rooftop Swimming Pool Depth as a Tuned Liquid Damper on Seismic Building Deflection Using Response Spectrum Analysis - Rosediana, Risky Andayani; Supriadi, Bambang; Siswosukarto, Suprapto (ASTONJADRO, 2025)
Tuned Liquid Damper (TLD) is a control system used to reduce structural vibrations in buildings or other structures (Hochrainer & Ziegler, 2006). One innovative use of this control system is a rooftop swimming pool (JIN et al., 2023). Research on utilizing pools as TLDs has been conducted, but no study has specifically focused on selecting the optimal depth of a rectangular rooftop swimming pool in irregular buildings. This study aims to analyze the influence of the selection of rooftop swimming pool depth on an irregular building structure's deflection. The analysis was conducted using ETABS, with the object being a 10-story hotel building with 2 basements. The existing swimming pool, measuring 16.25 x 4.85 meters and located on the rooftop, was analyzed with 3 different depth variations. The swimming pool was modeled using a spring mass model as a dynamic load according to ACI 350.3-2020. The analysis was carried out using the response spectrum method with parameters based on the building's location. The analytical findings reveal that the swimming pool depth can influence its performance as a tuned liquid damper (TLD) in an uneven building construction. The research revealed that model 3 had the least maximum displacement, with a reduction of 2.72% in the x-direction and 3.27% in the y-direction. It can be inferred that in the examined building, a swimming pool with a depth of 2 meters (model 3) is more successful at decreasing displacement, particularly in the y-direction.